SAR AND ITS IMPLICATIONS ON BIODIVE RESOURCES CONSERVATION IN WASUR NATIONAL PARK AREA, PAPUA - Simbiak, Maikel (Jurnal Ilmu Pendidikan Indonesia, 2021)
The landscape ethnoecological study approach also explores the significance of local systems in understanding ecological sustainability, including its implementation in biocultural conservation education. In this view, a study has been carried out on the traditions of the indigenous people of Wasur Village in Wasur National Park, regarding the practice of sar rituals and their relationship with education in Wasur National Park for biodiversity conservation to obtain an initial view from a biological perspective. This study uses an ethnological study approach with data collection through free interview techniques to key informants, library surveys, and free lists. The results of interviews with key informants revealed that the sar tradition is a ritual of respecting relatives who have died through a prohibition on the use of all forms of resources on family land that was left behind for a thousand days of mourning. Based on the literature survey, it was found that the period of a thousand days can support the regeneration of several specific macropod species in the Trans Fly area such as Dorcopsis spp, Macropus agile, and Thylogale spp. Sar is an example of a sasi system known by several tribes on the north coast of Papua which is promoted as culture-based conservation